Perspektif Mahasiswa tentang Rasa Puas (Santuṭṭhi) terhadap Pacar: Studi Kasus Mahasiswa STABN Sriwijaya Semester VIII Tahun Akademik 2022/2023 - Metta Cris Angel; Muawanah Muawanah; Nyoto Nyoto (Jurnal Pelita Dharma, 2023)
Humans are social beings who cannot live alone and cannot be separated  from the influence of other humans because humans need and influence one  another. One of the relationships that are owned is a relationship of love or  courtship. Dating raises several problems, such as at STABN Sriwijaya  Tangerang Banten, it was found several cases of students, especially in the VIII  semester of the 2022/2023 Academic Year, who felt dissatisfied in being in a  relationship, so they changed girlfriends, but there were also students who had  been in relationships for a long time. The purpose of this research is to describe  students' perspectives about satisfaction (santuṭṭhi) to partner for students of  STABN Sriwijaya semester VIII for the 2022/2023 Academic Year. This study uses a qualitative approach with a case study model. The  informants in this study are students of STABN Sriwijaya semester VIII for the  2022/2023 academic year who are Buddhists. Data collection techniques used,  namely observation, interviews, and documentation. Data were analyzed using the  Miles, Huberman, and Saldana models. The data validity technique was carried  out by testing credibility, transferability, dependability, and confirmability. The results of this study concluded (1) Student perspectives about santuṭṭhi  to girlfriends by STABN Sriwijaya students in semester VIII of the 2022/2023  academic year consisting of goals, knowing about santuṭṭhi, meaning, and  importance. The goals of having a romantic relationship include: looking cool,  motivation to study or study, desire, marriage, encouragement, filling in  deficiencies, and finding partners who share the same beliefs. Then students know  or not about santuṭṭhi data obtained include: satisfied with what is owned and do  not know. Students' understanding of santuṭṭhi is the special person we choose,  not feeling lonely, as a home, not there, learning together, encouragement for life,  a place to tell stories of complaints, life partners, family, and motivation. Then  according to students feeling satisfied or santuṭṭhi it is important to have; (2)  Student constraints in expressing satisfaction or santuṭṭhi to boyfriend consists of  personal character, communication problems, not giving a sense of comfort,  changes in the nature of the partner, people talk, differences in thoughts, and  stubbornness; (3) The way students express satisfaction or santuṭṭhi to partners  include: giving gifts, appreciating partners, paying attention, making partners  happy, concrete actions, improving oneself, asking for blessings, and conveying  them directly. Keywords: Perspective, Student, Santuṭṭhi